2012
DOI: 10.3233/jad-2011-111418
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Plasma Aβ as Predictor of Alzheimer's Disease in Older Individuals Without Dementia: A Population-Based Study

Abstract: Amyloid-β (Aβ) pathology is a major component in the mechanisms behind Alzheimer's disease (AD). Measurement of Aβ(42) in cerebrospinal fluid predicts cognitive decline in patients with mild cognitive impairment and identifies AD in patients with dementia. However, studies on Aβ in plasma are contradictory. In this prospective population-based study, plasma Aβ(42) and Aβ(40) were measured at baseline in 730 adults aged 70 years or older and without dementia. After five years, plasma levels were analyzed again … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 39 publications
3
18
1
1
Order By: Relevance
“…The study of Okereke et al [64] found that a decrease in Aβ 1-42 /Aβ 1-40 in the repeated plasma measurement was associated with greater cognitive decline. Lastly, studies reported by Hansson et al [29] and Toledo et al [10] found that during follow-up of 324 subjects for 5 years in the former and 613 subjects for 2 to 3 years in the latter study, there was an increase of Aβ 1-40 and Aβ 1-42 , whereas Aβ 1-42 /Aβ 1-40 decreased.…”
Section: Association Of Aβ With Ad and Cerebrovascular Diseasementioning
confidence: 80%
See 2 more Smart Citations
“…The study of Okereke et al [64] found that a decrease in Aβ 1-42 /Aβ 1-40 in the repeated plasma measurement was associated with greater cognitive decline. Lastly, studies reported by Hansson et al [29] and Toledo et al [10] found that during follow-up of 324 subjects for 5 years in the former and 613 subjects for 2 to 3 years in the latter study, there was an increase of Aβ 1-40 and Aβ 1-42 , whereas Aβ 1-42 /Aβ 1-40 decreased.…”
Section: Association Of Aβ With Ad and Cerebrovascular Diseasementioning
confidence: 80%
“…Different measures of plasma Aβ have been associated with progression to dementia (Table 4): high baseline Aβ 1-42 [30,57], low baseline Aβ 1-42 /Aβ 1-40 [58,59], low baseline Aβ 1-40 or Aβ 1-42 [60], high baseline Aβ 1-40 [29], high Aβ 1-40 or low Aβ 1-42 /Aβ 1-40 [61] and low Aβ 1-40 in older subjects [62]. Finally, other studies found no associations of plasma Aβ levels with progression to dementia [10,13,63].…”
Section: Association Of Aβ With Ad and Cerebrovascular Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Using the same selection of prospective cohorts, we first extracted hazard ratios of incident AD or dementia and their 95% confidence intervals from minimally adjusted models comparing lowest versus highest quantiles (quartiles or tertiles) of plasma Aβ 1-42 levels, plasma Aβ 1-40 levels or plasma Aβ 1-42 /Aβ 1-40 ratio. In addition to our results and those published by Shah et al [15], and Lui et al [12], we contacted three previously published studies, including Shah et al, that had measured plasma Aβ levels, to obtain unpublished hazard ratios [13, 15, 30]. Lastly, we performed fixed- and random-effect meta-analyses, and evaluated heterogeneity using the I 2 measure.…”
Section: Methodsmentioning
confidence: 87%
“…Reduced CSF Aβ 42 levels is associated with an increased risk of progression of mild cognitive impairment (MCI) to AD (Diniz et al, 2008). Previous clinico and epidemiological studies have reported that increased Aβ 42 levels and lower plasma Aβ 42 :Aβ 40 ratio can be an indicator of a higher risk of progression from MCI to AD; though other studies have also found no association between plasma Aβ biomarkers and increased risk of progression (Hansson et al, 2012; Fei et al, 2011; Koyama et al , 2012; Gabelle et al, 2013). Previous studies investigated the levels of Aβ peptides in the CSF and plasma of LLD patients.…”
Section: Introductionmentioning
confidence: 88%